The effect of human PBMCs immobilization on their Аβ42 aggregates-dependent proinflammatory state on a cellular model of Alzheimer’s disease - Kot, Kateryna; Kot, Yurii; Kurbanov, Rustam; Andriiash, Hanna; Tigunova, Olena; Blume, Yaroslav; Shulga, Sergiy (Frontiers in Neuroscience, 2024)
The leading pathological mechanisms of Alzheimer’s disease are amyloidosis and inflammation. The presented work was aimed to study the effect of human peripheral blood mononuclear cells (hPBMcs) cells-matrix adhesion on their pro-inflammatory state in vitro. Although direct interaction of Аβ42 to PBMC is not a cellular model of Alzheimer’s disease, PBMCs may serve as test cells to detect Аβ42-dependent molecular effects in monitoring disease progression. Peripheral blood mononuclear cells (PBMCs) are used to assess changes in cytokines released in response to diseases or Alzheimer’s disease-specific cytotoxic molecules such as Aβ42. The effect of recombinant amyloid β-peptide rАβ42 on the concentration of endogenous amyloid β-peptide Aβ40 and pro-inflammatory cytokines TNFα and IL-1β in human peripheral blood mononuclear cells that were cultured in suspension and immobilized in alginate microcarriers for 24 h were investigated. The localization and accumulation of Aβ40 and rAβ42 peptides in cells, as well as quantitative determination of the concentration of Aβ40 peptide, TNFα and IL-1β cytokines, was performed by intravital fluorescence imaging. The results were qualitatively similar for both cell models. It was determined that the content of TNFα and Aβ40 in the absence of rAβ42 in the incubation medium did not change for 24 h after incubation, and the content of IL-1β was lower compared to the cells that were not incubated. Incubation of cells in vitro with exogenous rAβ42 led to an increase in the intracellular content of TNFα and Aβ40, and no accumulation of IL-1β in cells was observed. The accumulation of Aβ40 in the cytoplasm was accompanied by the aggregation of rAβ42 on the outer surface of the cell plasma membrane. It was shown that the basic levels of indicators and the intensity of the response of immobilized cells to an exogenous stimulus were significantly greater than those of cells in suspension. To explore whether non-neuronal cells effects in alginate microcarriers were cell-matrix adhesion mediated, we tested the effect of blocking β1 integrins on proamyloidogenic and proinflammation cellular state. Immobilization within alginate hydrogels after incubation with the β1 integrins blocking antibodies showed a remarkable inhibition of TNFα and Aβ40 accumulation in rAβ42-treated cells. It can be concluded that activation of signal transduction and synthesizing activity of a portion of mononuclear cells of human peripheral blood is possible (can significantly increase) in the presence of cell-matrix adhesion.